The Approach and Importance of Urban Drainage from The Past to The Present - Seçkin, Nazire Papatya (İstanbul Üniversitesi, 2024)
Urban drainage and basic infrastructure systems, including the collection and controlled management of rainwater and wastewater, have been important throughout history. The origin of well-designed systematic drainage systems dates back to the Bronze Age. This systematic drainage design has continued to evolve over time. The common denominator of these systems is the efficient use of natural resources and the creation of liveable and resilient living spaces, which form the basis of the urban drainage technologies used today. It is clear that sewerage and drainage systems in cities are very important and will be an important part of future urban planning. Today, urban drainage and water management has to meet expectations beyond its historical importance due to concepts such as urbanisation, climate change, and energy conservation. Therefore, sustainable drainage systems are gaining attention for their ability to reduce carbon footprints, improve surface water runoff, and control flood risk. This article discusses the basic principles of drainage and assesses how important it has been for settlements throughout history and how it should be dealt with in the future using new concepts.
Keywords: Architecture (Other); Mimarlık (Diğer)